2015
DOI: 10.1016/j.jtbi.2015.09.033
|View full text |Cite
|
Sign up to set email alerts
|

On robustness of phase resetting to cell division under entrainment

Abstract: The problem of phase synchronization for a population of genetic oscillators (circadian clocks, synthetic oscillators, etc.) is considered in this paper, taking into account a cell division process and a common entrainment input in the population. The proposed analysis approach is based on the Phase Response Curve (PRC) model of an oscillator (the first order reduced model obtained for the linearized system and inputs with infinitesimal amplitude). The occurrence of cell division introduces state resetting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…In the present case, phase resetting (switching from the high to the low state) is also probably dependent on cell division, as shown in Figure 4b. It has been previously analytically demonstrated that, phase resetting can be achieved through cell division for a population of biological oscillators under entrainment (Ahmed et al, 2015). In the present study case, it can be suspected that cell division is one of the main components driving the relaxation process profile from the high to the low state, with at least two subpopulations of cells exhibiting different growth rates.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, phase resetting (switching from the high to the low state) is also probably dependent on cell division, as shown in Figure 4b. It has been previously analytically demonstrated that, phase resetting can be achieved through cell division for a population of biological oscillators under entrainment (Ahmed et al, 2015). In the present study case, it can be suspected that cell division is one of the main components driving the relaxation process profile from the high to the low state, with at least two subpopulations of cells exhibiting different growth rates.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, phase resetting (switching from the high the low state) has indeed been shown to be dependent on cell division (Figure 4B). It has been previously demonstrated analytically that for a population of biological oscillator under entrainment, phase resetting can be achieved through cell division [41]. In our case, it is indeed suspected that cell division is implied into the relaxation from the high to the low state, with at least two subpopulation of cells exhibiting different growth rate.…”
Section: Discussionmentioning
confidence: 58%
“…The magnitude of this jump is phase dependent, that is, the same stimulus affects oscillator differently at different parts of its cycle. The correspondence between the phase and its jump is described by the phase response (resetting) curve (PRC), which can be considered as a counterpart of the impulse response function in linear systems and used as a control tool [90][91][92][93]. The reader is referred to [91,93] for the relevant mathematical theory.…”
Section: Network Of Oscillatorsmentioning
confidence: 99%